2016
DOI: 10.3892/etm.2016.3926
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ulinastatin, a human urinary protease inhibitor, on heatstroke-induced apoptosis and inflammatory responses in rats

Abstract: Abstract. Ulinastatin has been demonstrated to protect against heatstroke by reducing cerebral ischemia and damage in rats. In order to extend these observations, apoptosis and systemic inflammatory responses were assessed in rats treated with ulinastatin prior to the initiation of heatstroke. Following the onset of heatstroke, histological analysis revealed that the hippocampal tissues displayed edema and damage. In addition, upregulation of malondialdehyde, inducible nitric oxide synthase (iNOS) and reactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…However, it remains uncertain whether ulinastatin can be recommended as a standard medication for and ARDS. In animal models, ulinastatin attenuates the pathophysiological process of acute lung injury induced by lipopolysaccharide, scald injury, phosgene and seawater, among other injuries [23, 24, 7173]. These benefits are mainly associated with inhibiting the activation of neutrophils, blocking nuclear factor-κB pathway, which plays a critical role in the regulation of pro-inflammatory (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it remains uncertain whether ulinastatin can be recommended as a standard medication for and ARDS. In animal models, ulinastatin attenuates the pathophysiological process of acute lung injury induced by lipopolysaccharide, scald injury, phosgene and seawater, among other injuries [23, 24, 7173]. These benefits are mainly associated with inhibiting the activation of neutrophils, blocking nuclear factor-κB pathway, which plays a critical role in the regulation of pro-inflammatory (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α, IL-1β, IL-6), down-regulate chemokines (e.g. IL-8, macrophage inflammatory protein-2), and increases neutrophils apoptosis [5, 23, 24, 67, 68, 7173]. In theory, ulinastatin could be a new option in ARDS treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent studies indicated that apoptosis in the hippocampus of gerbils increased after cerebral ischemia, while UTI treatment inhibited Bax molecule expression and increased Bcl-2 expression in ischemia-induced apoptosis in hippocampus and decreased the TUNEL+ and caspase-3+ cells in the hippocampal CA1 region induced by cerebral ischemia, thus improving ischemia-induced short-term memory impairment ( 9 ). UTI reduced the heatstroke-induced Bax/Bcl-2 ratio and caspase-3 levels in brain cells and inhibited cell apoptosis during cerebral injury ( 10 ). In this study, the TUNEL results showed that obvious renal tubular epithelial cell apoptosis occurred after 7 days of UUO surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It is applied clinically for the treatment of acute pancreatitis and extracorporeal circulation injury and the prevention of shock and surgical invasion. Recent studies indicate that UTI inhibited cell apoptosis during brain injury ( 9 , 10 ) and had a protective function in various acute renal injuries ( 11 , 12 ). In addition, it has been reported that UTI inhibited lung ( 13 ) and renal ( 14 ) fibrosis; however, the specific mechanism is still not clear.…”
Section: Introductionmentioning
confidence: 99%